The influence of additional bromelain enzyme on feed for growth and utilization efficiency of Asian redtail catfish seed feed (Hemibagrus nemurus) - Khairul Hadi; Bastian Bastian (Acta Aquatica: Aquatic Sciences Journal, 2026)
Asian redtail catfish (Hemibagrus nemurus) is a local fish in Riau Province which has high economic value and has the potential to be developed. This study aims to find out the influence of adding bromelain enzymes on feed for the growth and utilization efficiency of Asian redtail catfish seed feed. The experimental design used a Completely Randomized Design (CRD) with five treatments and three replications, namely A = control (0.0%), B = bromelain enzyme at a dose of 1.0%, C = 1.5%, D = 2.0 % and E = 2.5 %/g feed. The results showed that the addition of the bromelain enzyme to the feed had no significant influence on the growth and efficiency of the utilization of the Asian redtail catfish seed feed. The best addition of bromelain enzymes to feed was a dose of 2.0%/g feed which resulted in an absolute weight growth of 3.03 ± 0.2 g, an absolute length of 1.43 ± 0.2 cm, a specific growth rate of 4.31±1.5%/day, feed utilization efficiency was 57.3 ± 8.8 % and survival rate was 83.3 ± 11.5 %. Keywords: Asian Redtail Catfish; Bromelin Enzyme; Growth